2022
DOI: 10.37802/jamb.v3i2.280
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Customer Delight, Brand Image, and Product Innovation on The Purchase Decision of The Erigo Brand in The City of Surabaya

Abstract: This study aims to determine the effect of customer satisfaction, Brand image, and Product innovation on consumer Purchasing of Erigo brand products in Surabaya. This type of research is quantitative research. The population is all customers of the Erigo brand in Surabaya. The number of samples taken is 100 respondents who are taken incidentally. The sampling technique used is the prior probability sampling technique; this technique is randomization or coincidence. The data collection method used is a survey w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
0
0
Order By: Relevance
“…Lien et al (2015) highlight that brand image, perceived price, and perceived value are critical determinants that directly influence purchase intentions. Similarly, Mujanah and Satriatama (2022) found that brand image significantly affects purchasing decisions (Mujanah and Satriatama, 2022). Moreover, Tannady et al (2023) state that brand image and product quality significantly affect purchasing decisions (Tannady et al, 2023).…”
Section: The Relationship Brand Image and Purchasing Decisionmentioning
confidence: 94%
“…Lien et al (2015) highlight that brand image, perceived price, and perceived value are critical determinants that directly influence purchase intentions. Similarly, Mujanah and Satriatama (2022) found that brand image significantly affects purchasing decisions (Mujanah and Satriatama, 2022). Moreover, Tannady et al (2023) state that brand image and product quality significantly affect purchasing decisions (Tannady et al, 2023).…”
Section: The Relationship Brand Image and Purchasing Decisionmentioning
confidence: 94%
“…Building long-term customer relationships is difficult when: Expectations and needs are not fully understood. next customer Management, the company must understand the wants and needs of its customers and can use existing resources to satisfy and retain customers [12].…”
Section: Article Info Abstractmentioning
confidence: 99%